2014
DOI: 10.1371/journal.pone.0092016
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Nursing Home Residents with Dementia: Validation of the German Version of the ICECAP-O

Abstract: ObjectivesTo validate the ICECAP-O capability wellbeing measure’s German translation in older people with dementia living in a nursing home, and to investigate the influence of proxy characteristics on responses.MethodCross-sectional study. For 95 residents living in a German nursing home, questionnaires were completed by nursing professionals serving as proxy respondents. We investigated the convergent validity of the ICECAP-O with other Quality of Life (Qol) measures, the EQ-5D extended with a cognitive dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 53 publications
10
52
2
Order By: Relevance
“…The average ICECAP-O tariff score found in this study within a nursing home setting (0.61) was comparable to the scores reported in a Dutch study performed in nursing homes (0.63) [28] and in a German study also performed in nursing homes (0.63) [30], and was substantially lower than the score for community-living elderly, where the average scores ranged between 0.81–0.84 [22] [27] [31] [32] [37–41]. These findings support the reliability of our results.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The average ICECAP-O tariff score found in this study within a nursing home setting (0.61) was comparable to the scores reported in a Dutch study performed in nursing homes (0.63) [28] and in a German study also performed in nursing homes (0.63) [30], and was substantially lower than the score for community-living elderly, where the average scores ranged between 0.81–0.84 [22] [27] [31] [32] [37–41]. These findings support the reliability of our results.…”
Section: Discussionsupporting
confidence: 85%
“…The same finding was observed in the Dutch and German ICECAP-O validation studies in which no correlation with the dimension “security” was found [29, 30]. This might be because people with dementia do not generally worry about the future past a certain point, [41].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…One study indicated that the test-retest reliability of ASCOT after 74 days was acceptable [13]. Other studies have shown that both ICECAP-O and ASCOT are moderately to strongly associated with not only general quality-of-life scales but also the EQ-5D, activities of daily living (ADL) limitations, illness, and depressive symptoms [6,13,15,[20][21][22][23][24][25][26][27]. There is some evidence that compared with the EQ-5D, ICECAP-O and ASCOT are equally or strongly associated with the quality of care services and the intensity of care, as measured by hours delivered [6,21,23,28].…”
Section: Introductionmentioning
confidence: 99%